2022
DOI: 10.1007/s11191-022-00367-7
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Civil Scientific Literacy in China from the Perspective of Science Education

Abstract: On 25 June 2021, the State Council issued the new Outline of the National Action Scheme for Scientific Literacy for All Chinese Citizens (2020–2035) (Outline of Scientific Literacy). In order to provide reference for its implementation, this study analyzes the achievements and obstacles in the implementation of the old Outline of Scientific Literacy (2006–2010-2020) based on the results of all previous surveys on civic scientific literacy (CSL) in China and from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Regarding gender differences in scientific information literacy, men have more positive attitudes toward technology and tend to perceive themselves as more competent than women (Cai et al, 2017), leading to differences in self-reported results. The age and education differences in scientific information literacy found in this study also echo pre-vious scientific and information literacy studies (Wang et al, 2022). In addition, the findings might reflect the characteristics of marginalized groups in scientific information dissemination.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Regarding gender differences in scientific information literacy, men have more positive attitudes toward technology and tend to perceive themselves as more competent than women (Cai et al, 2017), leading to differences in self-reported results. The age and education differences in scientific information literacy found in this study also echo pre-vious scientific and information literacy studies (Wang et al, 2022). In addition, the findings might reflect the characteristics of marginalized groups in scientific information dissemination.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…The main effects test of the meta-analysis showed that adding feedback to human-machine interaction could enhance learners’ learning achievement and knowledge retention effects, consistent with the findings of many previous empirical studies ( VanLehn, 2011 ; Steenbergen-Hu and Cooper, 2014 ; Kulik and Fletcher, 2016 ). First, human-machine interaction feedback might create an adaptive learning environment for students, which could help improve learning achievement and knowledge retention ( Wang and Chen, 2022 ). Human-machine feedback focused on difficult knowledge to help students with highly constrained tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of feedback form, static feedback was significantly more effective in promoting learning effort than dynamic feedback. Dynamic feedback relied on the adaptive technology of artificial intelligence, which obtained learners’ behavioral, emotional, and cognitive states in real-time and provided students with feedback on precise learning resources and learning paths, and learners’ learning behaviors were manipulated by the intelligent learning environment, resulting in learners’ over-reliance on machines, passive acceptance of feedback information in the learning process, and lack of cognitive integration of feedback information, which affected learners’ learning effort to some extent ( Baker, 2016 ; Wang and Chen, 2022 ). Therefore, in the process of human-machine interaction feedback, it was important to strengthen the attention to the feedback process and mechanism, not to aggravate students’ dependence on the machine by emphasizing human-machine interaction feedback, to strengthen learners’ subjectivity from the level of feedback mechanism, and to support learners’ cognitive integration of feedback information, and then to actively regulate motivation, take action, and enhance learning effort.…”
Section: Discussionmentioning
confidence: 99%
“…In the annual reports of 2009 and 2013, it pointed out the new requirements of information technology on the development of personal literacy, and in the annual reports of 2013 and 2015, it emphasized that students should develop various qualities commensurate with the needs of the labor markets, which further enriched the framework of core competencies. In 2004, UNESCO published "Developing Key Competencies in Education: Some Lessons from International and National Experience" as an important achievement of participating in the DeSeCo project, which put forward five pillars for lifelong learning: learning to seek knowledge, learning to do things, learning to coexist, learning to develop, and learning to change, which are also "the essential basic qualities of citizens in the 21st century" [17,36]. On the basis of absorbing the achievements of the DeSeCo project of OECD, according to the needs of the characteristic development of European education and the background of the knowledge economy, the European Union (EU) proposed the goal of building a core competence system in the context of talent centered on "competence" [37] and published "Key Competences for Lifelong Learning: A European Reference Framework" in 2005.…”
Section: The Framework Of Core Competenciesmentioning
confidence: 99%